Academic Inculcating Behavior Scale and Validation using CSE and PsyCap in Diverse Faculty Members - Bhanthumnavin, Duchduen (International Journal of Engineering and Technology, 2018)
Academic Inculcating Behavior Scale (AIB) for faculty members in university was constructed for assessing and developing university lecturersâ€™ quality. There were four studies with the total sample of 828 university faculty members in Thailand. Ninety items were assembled, but only 31 items were selected by a group of educational-behavioral science experts. In study1 with 100 respondents, 25 out of 31 items met the criteria for item quality.Â Results from EFA in study 2 using 300 new respondents revealed a three-factor model (4 items for giving positive reinforcement, 3 items for giving social support, and 4 items for modeling and preventive action) with the total of 11 items and with 59.131% of the total variance accounted for. This model was confirmed by CFA with another 300 respondents in study 3. In study 4, using 128 respondents, criterion-related validity of the AIB scale score was demonstrated by the predictive power of four independent variables by performing multiple regression analysis. Three independent variables which were positively related to AIB were CSE, PsyCap, and level of education of the respondents. Furthermore, it was found that faculty members with doctoral degree reported higher score of AIB than the ones with Masterâ€™s degree. The results showed that AIB measure has acceptable qualifications. However, more predictors of AIB should be investigated and confirmed by experimental studies. Consequently, the necessity to carry out intervention program for faculty members can be met with success. This will benefit the students, as well as ensuring that higher educational institutions can perform their expected functions. Â Â Â Â Â